A pathoconnectome of early neurodegeneration: Network changes in retinal degeneration. (October 2020) - Pfeiffer, Rebecca L.; Anderson, James R.; Dahal, Jeebika; Garcia, Jessica C.; Yang, Jia-Hui; Sigulinsky, Crystal L.; Rapp, Kevin; Emrich, Daniel P.; Watt, Carl B.; Johnstun, Hope AB; Houser, Alexis R.; Marc, Robert E.; et al.
Abstract: Connectomics has demonstrated that synaptic networks and their topologies are precise and directly correlate with physiology and behavior. The next extension of connectomics is pathoconnectomics: to map neural network synaptology and circuit topologies corrupted by neurological disease in order to identify robust targets for therapeutics. In this report, we characterize a pathoconnectome of early retinal degeneration. This pathoconnectome was generated using serial section transmission electron microscopy to achieve an ultrastructural connectome with 2.18nm/px resolution for accurate identification of all chemical and gap junctional synapses. We observe aberrant connectivity in the rod-network pathway and novel synaptic connections deriving from neurite sprouting. These observations reveal principles of neuron responses to the loss of network components and can be extended to other neurodegenerative diseases. Highlights: The first ultrastructural pathoconnectome of a degenerating neural network. Rewiring of retinal networks occurs prior to complete loss of afferent input. Neurites extended by retinal neurons synapse with expected and novel partners. Novel gap junctions are formed by rod bipolar cells early retinal degeneration.